FORMULATION AND STABILITY OF WHITE BIRD'S NEST (Collocalia fuchiphaga) FACIAL SERUM AS ANTIAGING - Olipiya, Olipiya; Nurmaulawati, Rina; Cahyaningrum, Yanuar As’hari (Jurnal Farmasi & Sains Indonesia, 2024)
White swallow's nest (Collocalia fuchiphaga) is known to have benefits as an antioxidant so it can prevent skin aging. Serum preparations have advantages as skin care cosmetics because they contain active substances in high concentrations, are light and easy to apply. This study aims to make formulations, test physical quality, physical stability, irritation in test animals and test antioxidant activity using the DPPH method (2,2-diphenyl-1-picrylhydrazyl) as a facial serum containing white swallow's nest (Collocalia fuchiphaga) . In this study, a facial serum formulation containing white swallow's nest (Collocalia fuchiphaga) was prepared with various concentrations of 10%, 20% and 30%. The results showed that the 3 formulations had good physical quality tests based on the results of tests carried out in accordance with the standards. Based on the results of the physical stability test, the test results on pH, spreadability and viscosity showed no change in storage for 28 days. The antioxidant activity test results of the 3 formulations yielded IC50 values ​​of F1 (52.523 ppm), F2 (52.181 ppm), and F3 (51.165 ppm). The formulation of white swallow's nest serum (Collocalia fuchiphaga) does not cause primary irritation to rabbit test animals. Based on the results of the data analyzed statistically with a confidence level of 95%, the data obtained was p> 0.05 so that the 3 formulas showed no significant difference. It can be concluded from this study that facial serum containing white swallow's nest (Collocalia fuchiphaga) can be used as an antiaging preparation and does not irritate the skin.